Musical Arts Learning at Dahlia Indah Kindergarten: (Early Childhood Islamic Education, Faculty of Tarbiyah and Teacher Training) - Siti Erlina Sari, Indah Sri Sejati, Hilda Zahra Lubis (Pusdikra-Publishing.com, 2023)
Abstract Abstract Music learning in kindergarten utilizes music media to be an important part in helping to achieve developmental goals. From the results of research at the Dahlia Indah Kindergarten, it was revealed that teachers have utilized various forms of music media in implementing learning activities. The development of music media by teachers includes modifying song lyrics, creating simple songs and utilizing rhythmic musical instruments in rhythmic and singing activities, as well as utilizing electronic developments in learning activities